PENGARUH PERSEPSI SISWA TENTANG KETERAMPILAN MENJELASKAN GURU DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Tarida Yuni Arta; Sri Kartikowati; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of students' perceptions of teachers' explaining skills and learning discipline on student achievement on economic subjects. The population is 195 students and sample is 66 students, taken by random sampling technique (Slovin's formula). Data is collected through technique of questionnaires and documentation. Data analysis used multiple regression analysis. The result showed that students' perceptions of teachers' explaining skills has a positive and significant effect on learning achievement. The same effect also happened positive and significant at learning discipline on learning achievement. Simultanly, the two variable’s have a contribution of 67.2% on students' achievement. It can be conclude tha students't learning achievement in the Economic subjects students will increase along with the better the students' perceptions of teachers' explaining skills and also the discipline of students at the learning time.Key words : Students' Perceptions of Teachers' Explaining Skills, Learning Discipline, Student Achievement